(untitled) (Plant Tissue Culture and Biotechnology, 2018)
A protocol for obtaining a ready source of protocorm-like bodies (PLBs) was developed in Vanilla planifolia. MS containing BA 1 mg/l, IBA 0.5 mg/l, tryptone/peptone 2 g/l and 2% sucrose was used to induce PLBs from axillary bud explants. PLB formation from the shoot/root tips involved the direct conversion of the apices without an intermediate callus stage. PLBs either directly developed into plantlet or produced secondary protocorm like bodies. Thin cell layer culture of protocorm like bodies can be used as a commercial application of tissue culture technology for mass micro-propagation. The details of production of PLBs and their transformations in culture are also discussed. The plantlets derived from PLB were rooted in culture and established in the field after hardening. Plant Tissue Cult. & Biotech. 28(1): 91-98, 2018 (June)